Evaluation of the Constitution of Pakistan: Historically Background and Issues of the Judiciary, Legislature and Executive - Dr. Muhammad Ramzan; Dr. Sapna Mumtaz; Shakila Hashim; Dr. Parveen Akhtar Kallu; Dr. Saima Iqbal; Muhammad Saad; Amina Kousar; Dr. Irfan Tauheed (Al-Qanṭara, 2022)
Most people now agree that democracy is the finest, most workable, and fair form of government currently in use. Parliament is an essential part of every democratic government since it serves as the people's voice. The system requires free and fair elections, political liberty, and journalistic freedom. Uncorrupted elections are crucial to guaranteeing fair representation of the people. In a democratic government, the people's well-being is guaranteed through the legislative process. The democratic process was strongly supported by the government of Pakistan. The people of Pakistan and their elected representatives have been instrumental in the country's move toward democracy. Many military and civilian dictators have stymied Pakistan's progress toward a more democratic and parliamentary culture throughout the country's constitutional history. In reality, the public has generally accepted military control, and military authority has always stymied the development of civilian administration. In order to promote Pakistan's democracy, this report will shed light on a complete performance evaluation of the country's judicial system and parliament. Secondary data, such as books, journals, papers, and articles, were used in this research. This research is both analytical and descriptive in character. Key Words: Judiciary, Legislative Actions, Supreme Court, Historical, Constitution, "Basic Structure", Martial Law